Ethnoecology of home garden landscapes on Seliu Island, Belitung District, Indonesia - DOKI EFENDI; TATIK CHIKMAWATI; SULISTIJORINI SULISTIJORINI; NINA RATNA DJUITA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Efendi D, Chikmawati T, Sulistijorini, Djuita NR. 2024. Ethnoecology of home garden landscapes on Seliu Island, Belitung District, Indonesia. Biodiversitas 25: 1304-1319. Seliu Island, Belitung District, Indonesia, once famous for its copra production, is now a popular tourist destination for its mangoes. People on this island use many plants from their home gardens, but more information about the diversity of plants in the landscape needs to be presented. This study explored the ethnoecology of the home garden landscape on Seliu Island to determine vegetation cover and its role. Research methods include interviews, cruising, and purposive sampling for vegetation inventory to calculate the Importance Value Index (IVI). The research results showed that 119 species belonging to 58 families were identified as growing in Seliu Island home gardens. Based on the habit type, herbaceous plants are the mostly found. Based on the aspect of utilization, medicinal plants are the most found plants. Ananas comosus (L.) Merr. had the highest IVI (14.65). People use seven parts of plants for medicinal purposes, and the leaves are the most widely used part. Home gardens on Seliu Island have social, economic, cultural, and ecological functions. Plant diversity in home gardens on Seliu Island must be preserved and improved, considering that Seliu Island is separated from the main island, Belitung Island, so plants' availability must be maintained.